Compreensão e uso de estratégias de representação do discurso do outro na escrita de adolescentes - Vilma de Sousa (2006)
This paper evaluates the speech performance of a group of adolescents from lower class families in their last years of basic schooling in public schools, having as background the meaning assigned by the subjects to the writing culture and as mediating tools for the development of investigation-intervention the ways of representing the discourse of the other in journalistic genres. In looking into the processes and products of writing use was made of Bakhtin´s concepts of dialogism, polyphony and discursive genre, in connection with Vygotsky´s ideas regarding the social origin of language, and the role of mediation in learning. The concept of heterogeneity as advocated by Authier-Revuz and currently used in different trends of discourse analysis and Ducrot´s contribution about the linguistic marks of polyphony were applied to the analysis of the texts and taken into account in the pedagogical intervention process. The field work brought together observation, intervention and reflection, drew on the active participation of the subjects in reading and writing workshops and individual interviews. It involved the preparation and use of supporting teaching material, the production of texts by the subjects as well as an analysis of the products and processes of writing. To an extent, a experiment in didactic transposing of some written journalistic genres was conducted on the basis of didactic sequences as proposed by DOLZ, NOVERRAZ and SCHNEUWLY (2004). Throughout the process, the subjects were invited to invest in the conscious control of their own discursive activity, elaborating and re-elaborating texts in the genres chosen as learning object the journalistic news, the interview and the opinion article with emphasis on the marks of enunciation and the ways of representing the discourse of the other. Inroads were also made on the fictional narrative as well as experiments with translating oral into written reports with the aim of working the oral-written relationship and making it easy to characterize the genres under scrutiny. In order to approach the conditions favoring the production of writing to the social practices of language the investigation- intervention work was developed within the context of an NGO actively involved in adolescent education (Instituto de Adolescentes Voluntários IAV) and had as its ultimate goal the publication of a journal. It was therefore about writing in order to learn to write, to investigate how to teach writing as much as interfering in the community by means of concretely situated language actions.